Impact of specialization in gynecology and obstetrics departments on pregnant women's choice of maternity institutions - Yoshimi Adachi; Hiroyasu Iso; Junyi Shen; Kanami Ban; On Fukui; Hiroyuki Hashimoto; Takako Nakashima; Kenichiro Morishige; Tatuyoshi Saijo (Health Economics Review, 2013)
In April 2008, specialization in gynecology and obstetrics departments was introduced in the Sennan area of Osaka prefecture in Japan that aimed at solving the problems of regional provisions of obstetrics services (e.g., shortage of obstetricians, overworking of obstetricians, and provision of specialist maternity services for high-risk pregnancies). Under this specialization, the gynecology and obstetrics departments in two city hospitals were combined and reconstructed into two centers, i.e., the gynecological care center in Kaizuka City Hospital and the prenatal care center in Izumisano City Hospital. This paper investigates to what extent and how this specialization affected pregnant women's choices of the prenatal care center and other maternity institutions. We used birth certificate data of 15,927 newborns from the Sennan area between April 1, 2007 and March 30, 2010, for Before and After Analysis to examine changes in pregnant women's choices of maternity institutions before and after the specialization was instituted. Our results indicated that this specialization scheme was, to some extent, successful on the basis of providing maternity services for high-risk pregnancies at the prenatal care center (i.e., Izumisano City Hospital) and having created a positive effect by pregnant women to other facilities in the nearby area.
Keywords: 330; Specialization; Gynecology and obstetrics departments; Maternity facilities; Before and after analysis